The integration of the treatment for common mental disorders in primary care: experiences of health care providers in the MANAS trial in Goa, India - Pereira, Bernadette (BioMed Central, 2011)
BACKGROUND: The MANAS trial reported that a Lay Health Counsellor (LHC) led collaborative stepped care intervention (the "MANAS intervention") for Common Mental Disorders (CMD) was effective in public sector primary care clinics but private sector General Practitioners (GPs) did as well with or without the additional counsellor. This paper aims to describe the experiences of integrating the MANAS intervention in primary care. METHODS: Qualitative semi-structured interviews with key members (n = 119) of the primary health care teams upon completion of the trial and additional interviews with control arm GPs upon completion of the outcome analyses which revealed non-inferiority of this arm. RESULTS: Several components of the MANAS intervention were reported to have been critically important for facilitating integration, notably: screening and the categorization of the severity of CMD; provision of psychosocial treatments and adherence management; and the support of the visiting psychiatrist. Non-adherence was common, often because symptoms had been controlled or because of doubt that health care interventions could address one's 'life difficulties'. Interpersonal therapy was intended to be provided face to face by the LHC; however it could not be delivered for most eligible patients due to the cost implications related to travel to the clinic and the time lost from work. The LHCs had particular difficulty in working with patients with extreme social difficulties or alcohol related problems, and elderly patients, as the intervention seemed unable to address their specific needs. The control arm GPs adopted practices similar to the principles of the MANAS intervention; GPs routinely diagnosed CMD and provided psychoeducation, advice on life style changes and problem solving, prescribed antidepressants, and referred to specialists as appropriate. CONCLUSION: The key factors which enhance the acceptability and integration of a LHC in primary care are training, systematic steps to build trust, the passage of time, the observable impacts on patient outcomes, and supervision by a visiting psychiatrist. Several practices by the control arm GPs approximated those of the LHC which may partly explain our findings that they were as effective as the MANAS intervention arm GPs in enabling recovery.